2000
DOI: 10.1080/1028415x.2000.11747301
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting Effects of Early Environmental Stimulation on Cortical Spreading Depression in Normal and Early Malnourished Adult Rats

Abstract: We investigated the effects of early environmental stimulation on spreading depression in the cerebral cortex of male Wistar adult (90 day old) well-nourished (23% protein diet) and early malnourished (8% protein) rats. Environmental stimulation was performed during the suckling period or after weaning. Control rats were housed in a standard environment. Environmental stimulation after weaning produced a reduction of body weights in well-nourished rats, and an increase in wet, but not dry brain weights, in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
1
11
0
3
Order By: Relevance
“…Concerning nutritional deficiency, CSD-susceptibility was increased in rats malnourished early in life, as judged by its higher CSD velocities, in comparison to the well-nourished rats, confirming previous studies (Andrade et al 1990;Rocha-De-Melo and Guedes 1997;Santos Monteiro et al 2000;Amâncio-dosSantos et al 2006). Deficient myelination, increased brain cell packing density, altered neuron-to-glia ratio and synaptic neurotransmitters are the most suggested mechanisms to explain the effect of early malnutrition on cortical CSD (De Luca et al 1977;Rocha-DeMelo and Guedes 1997).…”
Section: Malnutrition-pe Interaction On Cortical Spreading Depressionsupporting
confidence: 89%
“…Concerning nutritional deficiency, CSD-susceptibility was increased in rats malnourished early in life, as judged by its higher CSD velocities, in comparison to the well-nourished rats, confirming previous studies (Andrade et al 1990;Rocha-De-Melo and Guedes 1997;Santos Monteiro et al 2000;Amâncio-dosSantos et al 2006). Deficient myelination, increased brain cell packing density, altered neuron-to-glia ratio and synaptic neurotransmitters are the most suggested mechanisms to explain the effect of early malnutrition on cortical CSD (De Luca et al 1977;Rocha-DeMelo and Guedes 1997).…”
Section: Malnutrition-pe Interaction On Cortical Spreading Depressionsupporting
confidence: 89%
“…Disturbances in cognitive development have also been associated with the deficiency of specific compounds of the breast milk, like polyunsaturated fatty acids (Lucas 1997). In addition, experimental results have unequivocally demonstrated that the cerebral cortex is very sensitive to nutritional and plasticity changes (Leuba and Rabinowicz 1979;Sirevaag et al 1988;Borba et al 2000;Santos-Monteiro et al 2000). These data collectively raise the question of how electrophysiological changes in energy-challenging phenomena like SD would be associated with these developmental disturbances.…”
Section: Discussionmentioning
confidence: 91%
“…During SD, the ECoG activity became depressed and the amplitudes and durations of the DC-recording accompanying SD ranged from -10 to -20mVand from 40 to 80s, respectively. After SD, electrographic cortical recovery took 5-10 min to be completed and usually an interval of at least 20 min between stimulations was kept, as usual (Guedes and Do Carmo, 1980;Santos-Monteiro et al, 2000;Guedes et al, 2002). These baseline SD-recordings are illustrated in the left part of each panel of Fig.…”
Section: Sd-features At the Baseline Recording Periodmentioning
confidence: 99%